Inflammatory cytokines in subarachnoid haemorrhage: association with abnormal blood flow velocities in basal cerebral arteries. Issue 4 (1st April 2001) - Fassbender, K; Hodapp, B; Rossol, S; Bertsch, T; Schmeck, J; Schütt, S; Fritzinger, M; Horn, P; Vajkoczy, P; Kreisel, S; Brunner, J; Schmiedek, P; et al.
Abstract : Subarachnoidal release of inflammatory cytokines (interleukin (IL)-1β, IL-6, and tumour necrosis factor (TNF)-α) was characterised in 35 patients with subarachnoid haemorrhage (SAH) and control subjects and compared with development of complicating haemodynamic abnormalities in basal cerebral arteries and clinical outcome. Serial analysis allowed the observation of a subacute response profile of these key mediators of inflammation in the subarachnoidal space. This compartmentalised inflammatory host response was closely associated in time and extent with development of increased blood flow velocities in the basal cerebral vessels as recorded by transcranial Doppler sonography. Moreover, intrathecal secretion of inflammatory cytokines was significantly increased in patients with poor clinical outcome. Together, these findings suggest a role of excessive compartmentalised inflammatory host response in pathogenesis of cerebrovascular complications after SAH.